THE ROLE OF NA-MONTMORILLONITE IN THE EVOLUTION OF COPPER, NICKEL, AND VANADYL GEOPORPHYRINS DURING DIAGENESIS - Foster N.S.; Day J.W.; Filby R.H.; Alford A.; Rogers D. (My University, 2002)
Sorption of a series of toluene-solvated porphyrins with differing structural characteristics and metallic centers [i.e. free-base, Cu(II), Ni(II) and VO(II)] onto Na-montmorillonite was measured to determine how this clay mineral might influence porphyrin pathways during diagenesis. In most instances, adsorption was adequately described by the Langmuir isotherm equation. The adsorption results were compared in two ways: (1) by the metallating ion, where predicted trends of the relative degree of adsorption are based on Buchler stability indices, and (2) by the structural type, where predicted trends of the relative degree of adsorption are based on the number and type of substituent groups and their corresponding steric and functional characteristics. The implications of macrocycle shape (planar, ruffle, and wave) are also discussed. In general, sorption affinity based on metallating ion followed the order: VO(II)~Ni(II)<Cu(II)<<Free-base. In terms of functional groups, sorption affinity generally followed the order: phenyl (meso)<ethyl<methyl<ester. Ruffled shapes generally sorb less than planar shapes. These sorption trends are used to explain how clay minerals might influence the selective sorption and decomposition of porphyrins in oil shales; how clay minerals may contribute to or be responsible for the decreasing Ni(II)/VO(II) ratios observed in the fossil record; and why clay minerals probably do not play a major role in the decreasing deoxophylloerythroetioporphyrin/etioporphyrin I (DPEP/ETIO) ratio observed in the maturing sedimentary environment.